2008
DOI: 10.1177/0748233708093781
|View full text |Cite
|
Sign up to set email alerts
|

JP-8 jet fuel exposure suppresses the immune response to viral infections

Abstract: The US Air Force has implemented the widespread use of JP-8 jet fuel in its operations, although a thorough understanding of its potential effects upon exposed personnel is unclear. Previous work has reported that JP-8 exposure is immunosuppressive. Exposure of mice to JP-8 for 1 h/day resulted in immediate secretion of two immunosuppressive agents, namely, interleukin-10 and prostaglandin E2. Thus, it was of interest to determine if jet fuel exposure might alter the immune response to infectious agents. The H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Previous studies with hydrocarbons have shown following direct exposure toxicological effects such as adverse effects in lung ventilatory function [17], immune dysfunction [18, 25], increased tumor formation [26], and suppressed immune response to viral infections [27]. In the current study, the F1 generation animals of jet fuel lineage showed an increase in the incidence of adult-onset disease/abnormalities including prostate disease, kidney disease, ovarian primordial follicle loss, polycystic ovarian disease, pubertal abnormalities, and an overall increase in total and multiple disease/abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with hydrocarbons have shown following direct exposure toxicological effects such as adverse effects in lung ventilatory function [17], immune dysfunction [18, 25], increased tumor formation [26], and suppressed immune response to viral infections [27]. In the current study, the F1 generation animals of jet fuel lineage showed an increase in the incidence of adult-onset disease/abnormalities including prostate disease, kidney disease, ovarian primordial follicle loss, polycystic ovarian disease, pubertal abnormalities, and an overall increase in total and multiple disease/abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models low toxicity of JP-8 has been reported to cause slight dermal irritation, weak dermal sensitization, respiratory tract sensory irritation, hearing loss, nephropathy, and immunosuppressive and neurobehavioral effects [24]. Previous studies have also shown adverse effects in lung ventilatory function [17], immune dysfunction [18, 25], increased tumor formation [26] and suppressed immune response to viral infections [27]. There are no reports regarding potential epigenetic transgenerational inheritance of disease from JP-8 exposed gestating females.…”
Section: Introductionmentioning
confidence: 99%
“…The report by Hilgaertner et al (2011) demonstrates JP-8-related immunosuppressive effects, including decreased spleen and thymus weights at exposure levels ≥1000 mg/m 3 and reduced IFN- γ production at doses ≥4000 mg/m 3 . Hilgaertner et al (2011) also indicated that these exposures were equivalent to aerosol exposures of 125 and 500 mg/m 3 in the early reports by Harris et al (1997, 2000a, 2000b, 2002, 2007, 2008). These results, which contrast with those in the present study evaluating the base jet fuel kerosene, suggest the possibility that the additives, and not the jet fuel kerosene, are primarily responsible for the immunosuppressive effects of JP-8 jet fuel.…”
Section: Discussionmentioning
confidence: 86%
“…A number of previous studies indicated that JP-8 is an immunotoxicant following nose-only inhalation (Harris et al, 1997, 2000a, 2000b, 2002, 2007, 2008), dermal exposure (Ramos et al, 2002, 2007; Ullrich, 1999; Ullrich and Lyons, 2000), and oral gavage (Keil et al, 2004; Peden-Adams et al, 2001). The inhalation and dermal studies of others implicated CMI as the primary target, while no effects on humoral immunity were observed on the T-dependent antibody response (TDAR) to KLH in the dermal studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation